PENGARUH INTELLECTUAL CAPITAL TERHADAP RETURN SAHAM DENGAN FIRM VALUE SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Sub Sektor Property dan Real Estate yang Terdaftar di BEI Periode 2017-2020) - Labiba, Fikriatul; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
The development of the business world today is progressing very rapidly and competition is so tight, in order to compete competitively, companies need to have strengths that include knowledge, experience, skills, reputation and also technological capabilities. The purpose of this study was to analyze and test the effect of intellectual capital on stock returns in the company through firm value. This research is an explanatory research. The population in this study is the Property and Real Estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Intellectual capital has a significant positive effect on Firm value, Intellectual capital has a positive but not significant effect on stock returns, Firm value has a significant positive effect on stock returns. The results of the indirect effect hypothesis test show that the Intellectual capital variable on stock returns through Firm value has a significant positive effect.